Neutrophil-to-lymphocyte ratio, monocyte-to-lymphocyte ratio, and platelet-to-lymphocyte ratio in different etiological causes of thyrotoxicosis - TAŞKALDIRAN, Işılay (Turk J Med Sci, 2019)
BACKGROUND/AIM: The most common causes of thyrotoxicosis include Graves’ disease (GD), toxic multinodular goiter (TMNG), toxic adenoma (TA), and subacute granulomatous thyroiditis (SAT). In our study, we aimed to see whether neutrophil‐to‐lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet‐to‐lymphocyte ratio (PLR), and mean platelet volume (MPV) may be helpful in the differential diagnosis of these diseases. MATERIALS AND METHODS: We retrospectively analyzed the hospital records of the Endocrinology Clinic of our hospital between 2016 and 2019. We included data from 66 GD, 37 TA, and 35 SAT patients. We compared the data with those of 35 healthy subjects as controls. RESULTS: NLR, MLR, and PLR were found to be higher in the SAT group when compared to other groups. The post hoc analysis of comparison of NLR, MLR, and PLR in each group showed that NLR and PLR were significantly different in the SAT group when compared to the GD, TA, and controls groups (P < 0.001, P = 0.003, and P < 0.001 for NLR respectively and P < 0.001 for PLR in all groups). MPV levels were different between groups (P = 0.007). However, the intergroup analysis (Tukey’s test) failed to show a statistically significant difference for any of the groups. In patients with SAT, PLR and NLR were significantly higher than in the GD, TA, and control groups. MLR was also higher in SAT when compared to other groups, but the difference was not statistically significant. CONCLUSION: High PLR and NLR may be helpful to differentiate SAT from GD and TA, the other common causes of thyrotoxicosis.